Design of an Optical Wireless Network Using Free Space Optics Technology (Fso), in 5g/6g Networks Environment - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2021)
We propose a free-space optical system for the current network topology of university campus buildings and the Astronomical Observatory, at Quito, Ecuador. Using wireless optical communication provides the advantages of a wireless environment and faster data transfer rate. The Free Space Optics (FSO) design considers the worst atmospheric condition (torrential rain and fog) where the visibility value is 770 meters. The obtained atmospheric-attenuation coefficient is 3.84 dB/Km. Link margin values calculated between 4.74 dB to 43.99 dB allow validating the FSO network design. The FSO cost implementation is almost equal than a fiber optic alternative, which makes this technology very attractive for Optical Wireless Communications (OWC) in the 5G/5GB/6G network environment. © 2021 IEEE.